The Influence of the Story DONI AND GIGINYA on Oral Hygiene Behavior in Preschool Children Banyuwangi - Haswita Haswita; Mila Mar’atus Sholihah; Roshinta Sony Anggari (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Oral hygiene problems that cause damage to the oral cavity in children in Indonesia are still high, reaching 57.6%. So it is very important to pay attention because this is an important growth stage. Damaged teeth can cause delayed tooth development in later life. The method of oral hygiene that attracts the attention of preschool children is the storytelling method. The aim of this research is to determine the effect of stories on oral hygiene behavior in preschool children. This method is quantitative research using a quasi-experimental design (one group pre-test and posttest). The population consisted of 50 individuals, and the sampling technique used was total sampling, using an observation checklist sheet to measure how to brush teeth. Statistical tests use the Wilcoxon Test. The results of the research showed that after the story was given, there was an increase, namely 30 children behaved good, 18 children behaved enough, and 2 children behaved poorly. Wilcoxon Signed Rank Test results with a value of p=000<0.05, the analysis shows that the story